Sekolah Sahabat Gawai: Pendampingan Kegiatan Belajar dari Rumah untuk Menjaga Kesehatan Siswa SMP Islam Dian Didaktika - Nurfitri Bustamam; Duma Lumban Tobing; Evin Novianti (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2021)
In the Academic Year 2020/2021 learning face-to-face for school students in most parts of Indonesia is prohibited to prevent the spread of coronavirus disease (COVID)-19. Instead, a school from home (SFH) is implemented. As a result, the use of gadgets by school students increases not only for learning activities, but also for communication, entertainment/recreation, and socializing. Excessive use of the gadget will increase the risk of developing health problems both physically and mentally. Based on this, the school collaborated with a team from the Faculty of Medicine and the Faculty of Health Sciences Universitas Pembangunan Nasional Veteran Jakarta to carry out community service activities with the theme "School of Gadget-Friendly.” This activity aimed to 1) Increase students' knowledge of health problems both physically and mentally due to excessive use of gadgets and 2) Students implement efforts to prevent/reduce the risk of health problems when they are using gadgets. Partners of this activity were students of Islamic Junior High School Dian Didaktika grades 8 and 9. Education to students by the team was carried out from the school studio using google meet. Before and after education, students were given a pre & post-test to measure the level of knowledge. A week later the students were asked to fill out a checklist related to their activities using the gadget. School teachers were also asked for their opinions regarding the activity. The results of this activity were an increase in students' knowledge regarding the use of gadgets and most students have made any efforts to stay healthy when using gadgets during SFH. The school teacher argued that this community service activity was a provision for students to be able to use gadgets wisely so that they remained healthy during SFH.